Effect of Student Evaluation of Teacher Based Feedback on Self-Disclosure of Secondary School Teachers - Patel, Nilesh Kumar; Awasthi, Poonam (EDUCARE, 2018)
ABSTRACT:Â Self-evaluation of teachers can be considered as a process of looking at teachersâ owns progress, development, and learning to determine what has improvement and what areas still need improvement. The research is aimed at finding out the effect of student evaluation of teacher based feedback on self-disclosure of secondary school teachers. This research is experimental in nature.Â Non-equivalent control group design, suggested by Donald T. Campbell & Julian C. Stanley (1963), was used for the experiment. Student evaluation of teacher based feedback was treatment and independent variable; self-disclosure of teachers was dependent variable; and pre â self-disclosure, pre-teaching effectiveness, and intelligence were considered as covariates. The sample of the study comprised of 70 secondary school teachers, and 220 students studying in secondary classes from purposively selected four schools of Indore city, India. The data for self-disclosure, teaching effectiveness, and intelligence were collected through standardized tools. One-way ANCOVA (Analysis of Covariance) and 2x2 factorial design ANCOVA were used for data analysis. Hypotheses were tested at level of significance with Î± = 0.05. It was found that the treatment has significant effect over self-disclosure of secondary school teachers when pre â self-disclosure was taken as covariate. The results also shown that self-disclosure was independent of the treatment, when intelligence and pre-teaching effectiveness was separately considered as covariates. In addition, the study of self-disclosure was also found independent of interaction between feedback and intelligence, when pre â self-disclosure was taken as covariate.KEY WORDS: Student Evaluation of Teachers; Assessment of Teaching; Assessment of Instruction; Self-Disclosure; Secondary School Teachers.Â Â About the Authors: Nilesh Kumar Patel is Principal at the Vidyasagar College, Indore City, India; Head of Department at the IGNOU (Indira Gandhi National Open University) Study Center 1558 (P); and VT (Visiting Team) member in NCTE (National Council for Teacher Education): A Statutory Body of Government of India, in New Delhi, India. Poonam Awasthi is M.Ed. Student at the Vidyasagar College DAU (Devi Ahilya University), Indore City, India. E-mail address: nktp12374@gmail.com and poonamt06@gmail.comSuggested Citation: Patel, Nilesh Kumar & Poonam Awasthi. (2018). âEffect of Student Evaluation of Teacher Based Feedback on Self-Disclosure of Secondary School Teachersâ in EDUCARE: International Journal for Educational Studies, Volume 10(2), February, pp.63-74. Bandung, Indonesia and BS Begawan, Brunei Darussalam: Minda Masagi Press owned by ASPENSI and BRIMAN Institute, ISSN 1979-7877. Article Timeline: Accepted (December 28, 2017); Revised (January 28, 2018); and Published (February 28, 2018).